2020
DOI: 10.1155/2020/2189189
|View full text |Cite
|
Sign up to set email alerts
|

Acute and Subchronic Toxicity Profile of a Polyherbal Drug Used in Sri Lankan Traditional Medicine

Abstract: A polyherbal drug composed of leaves of Murraya koenigii L. Spreng, cloves of Allium sativum L., fruits of Garcinia quaesita Pierre, and seeds of Piper nigrum L. is a popular drug which has been used by indigenous practitioners in Sri Lanka for the treatment of diabetes mellitus and dyslipidemia. The acute toxicity assessment was conducted, following a single oral dose of 0.25–2.0 g/kg in healthy rats, and rats were observed up to 14 days. The hot water extract (1.0 g/kg) and the water : acetone extract (0.5, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…47 High level of liver biomarkers is a valid indicator of liver damage. 48 The administration of plants extract for 28 days did not cause any noxious effect on liver and liver biomarkers as compared to the untreated group. The little alteration has no clinical importance because values recorded are within the normal range.…”
Section: Discussionmentioning
confidence: 87%
“…47 High level of liver biomarkers is a valid indicator of liver damage. 48 The administration of plants extract for 28 days did not cause any noxious effect on liver and liver biomarkers as compared to the untreated group. The little alteration has no clinical importance because values recorded are within the normal range.…”
Section: Discussionmentioning
confidence: 87%
“…Biochemical parameters suggested possible toxic effects of herbal medicines on liver and kidney function. Evaluation of liver and kidney function is very important because these two organs are mainly involved in body detoxification and homeostasis [ 61 , 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, their sub-chronic toxicity experiment showed that administering polyherbal black-pepper seed mixture (500, 1,000, and 1,500 mg/kg/b.w.) for 28 days did not alter the monitored biochemical, histological, and hematological parameters in the kidney and liver of diabetic rats [ 170 ].…”
Section: Toxicological Insights Of Black Pepper and Piperine: Preclin...mentioning
confidence: 99%